Pseudacteon Parasitoids of Azteca instabilis Ants in Southern Mexico (Diptera: Phoridae; Hymenoptera: Formicidae) - Brian V. Brown; Stacy M. Philpott (Psyche: A Journal of Entomology)
Three new species of the genus Pseudacteon are described, all from Chiapas, Mexico, and all of which are parasitoids of the ant Azteca instabilis. Sternite 6 of Pseudacteon dorymyrmecis Borgmeier is illustrated for the first time, and P. confusus Disney is synonymized with this species. The natural history of the Azteca-Pseudacteon interaction is described.